2023
DOI: 10.3390/cells12020216
|View full text |Cite
|
Sign up to set email alerts
|

Cissus quadrangularis (Hadjod) Inhibits RANKL-Induced Osteoclastogenesis and Augments Bone Health in an Estrogen-Deficient Preclinical Model of Osteoporosis Via Modulating the Host Osteoimmune System

Abstract: Osteoporosis is a systemic skeletal disease characterised by low bone mineral density (BMD), degeneration of bone micro-architecture, and impaired bone strength. Cissus quadrangularis (CQ), popularly known as Hadjod (bone setter) in Hindi, is a traditional medicinal herb exhibiting osteoprotective potential in various bone diseases, especially osteoporosis and fractures. However, the cellular mechanisms underpinning its direct effect on bone health through altering the host immune system have never been elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Five micrometer thick paraffin sections of testes were prepared, deparaffinized by dipping the glass slides in xylene for 10−15 min followed by a rinse with tri‐chlorotrifluoroethane (C 2 Cl 3 F 3 ) and dried by solvent evaporation. The specimen was given a surface conductive coat of gold (Au) for further insights 22 . For doing this, the backscattered electron (BSE) image has been used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five micrometer thick paraffin sections of testes were prepared, deparaffinized by dipping the glass slides in xylene for 10−15 min followed by a rinse with tri‐chlorotrifluoroethane (C 2 Cl 3 F 3 ) and dried by solvent evaporation. The specimen was given a surface conductive coat of gold (Au) for further insights 22 . For doing this, the backscattered electron (BSE) image has been used.…”
Section: Methodsmentioning
confidence: 99%
“…The specimen was given a surface conductive coat of gold (Au) for further insights. 22 For doing this, the backscattered electron (BSE) image has been used. The images were captured at low and high magnifications using by scanning electron microscope (FEI Nova NanoSEM 450).…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The body weight of all mice was recorded and then anaesthetized with Ketamine (100-150 mg/kg) and Xylazine (5-16 mg/kg) 37 for collecting blood via retro-orbital sinus. For serum isolation, the blood was allowed to clot in tubes by keeping it undisturbed at RT for 20 minutes.…”
Section: Blood Serum Collection and Tissue Harvestingmentioning
confidence: 99%
“…It has been observed that the ethanolic extract of C. quadrangularis contains flavonoids and phenolic substances with immunomodulatory potential that significantly inhibits bone resorption postovariectomy (Banu et al, 2012). In addition, our group recently reported that via modulating the immunoporotic potential of distinct immune cells (Th1, Th2, Th17, Treg, and Breg) C. quadrangularis administration has significantly enhanced the bone health in ovariectomized mice model (Azam et al, 2023). Native to the Indian subcontinent, Moringa oleifera , a member of Moringaceae family, is a fast‐growing, drought‐resistant tree and is one of the most nutritious food supplements.…”
Section: Plant‐derived Natural Products As Therapeutics Targeting Ost...mentioning
confidence: 99%